Monitoramento e avaliação de políticas públicas: análise da política de assistência estudantil do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Lima, Gillyane Lyndsay Gomes de (2020)
The present study had the purpose of analyzing the Student Assistance Policy of the Federal Institute of Education, Science and Technology of Paraíba (PAE-IFPB), with the objective of evaluating the process of reformulation of this Policy and, based on the results, proposing an approach monitoring for a permanent evaluation of the Student Permanence Support Program (PAPE). Therefore, it was necessary to analyze the reformulation of the PAE between the years 2016 and 2018, identifying the existence or not of monitoring and evaluation instruments. This work was organized in seven chapters, initially presenting the trajectory of student assistance policies in Brazil from the perspective of Kowalski (2012), going through Student Assistance at Federal Universities, carrying out a discussion on the National Assistance Program Student (PNAES). For a better understanding of PAE - IFPB it was necessary to discuss the historical path of the IFPB, as well as the PAE implemented in the institution. To carry out a more consistent analysis of the Student Assistance Policy developed at the IFPB, considerations about public policies were considered in the conception of the authors Guedelho (2017), Rodrigues (2008) and Condé (2013). To this end, this work presented a more attentive analysis of the process and possible consequences of the reformulation of the PAE-IFPB, making a comparison between the old policy (resolution No. 40 of May 2011) and the reformulated PAE-IFPB (resolution No. 25 June 2018). The research was developed in an exploratory descriptive character with a qualitative approach, presenting the semi-structured interview conducted with the operating managers of the PAE-IFPB as a data collection instrument, which supported the content analysis based on Bardin (2011) and the elaboration of the SWOT matrix. where the weaknesses, strengths, threats and opportunities of the policy investigated can be explained. A propositional profile was also privileged, once the results of the investigation found the absence of monitoring instruments for an evaluation of the Student Permanence Support Program, in which suggestions for a monitoring instrument that supported the evaluation of this Program were listed, for example. be the one with the largest financial investment and the first in the process of implementing the reformulated IFPB policy. Thus, the work sought to discover important analytical aspects that could suggest a more effective monitoring and evaluation in the perspective of improving the reformulated policy.